Influence of preparation and exposure periods of eluates from ocular prosthesis acrylic resin in human conjunctival cell line - da Silva, Emily Vivianne Freitas [UNESP]; Dos Santos, Daniela Micheline [UNESP]; Bonatto, Liliane da Rocha [UNESP]; Brito, Victor Gustavo Balera [UNESP]; de Oliveira, Sandra Helena Penha [UNESP]; Goiato, Marcelo Coelho [UNESP] (CMV Verlag, 2019)
Background: This study was undertaken to analyze if different preparation and exposure periods of eluates from ocular prosthesis acrylic resin influence the cytotoxicity for conjunctival cells. Methods: Twenty-four acrylic resin specimens were divided, according to the period of eluate exposure to Chang conjunctival cells (24 and 72 hours). Eluates were prepared in four different ways: 24, 48, and 72 hours of resin specimen immersion in medium and 24 hours of immersion in water, followed by 24 hours of immersion in medium. MTT assay was used to evaluate the cytotoxic effect. The production of IL-1β, IL-6, TNF-α, and chemokine macrophage inflammatory protein 1α was evaluated by ELISA, while the mRNA expression of type IV collagen (COL IV), transforming growth factor β (TGF-β), and matrix metalloproteinase 9 (MMP9) were evaluated by real-time RT-PCR technique. The statistical analysis was carried out using ANOVA with Bonferroni post-hoc test and the student’s t-test (p < 0.05). Results: Significant quantities of IL-6 (4.594 pg/mL) and mRNA expression of COL IV (1.58) were verified at 72 hours of eluate exposure to cells, as compared to 24 hours. After the 72-hour exposure of eluates to cells, lower cell proliferation (88.4%) and higher IL-6 quantities (12.374 pg/mL), as well as mRNA expression of COL IV (2.21), TGF-β (2.02), and MMP9 (5.75) were observed, which corresponded to 72 hours of a specimen immersed in medium. Conclusion: Longer periods of eluate preparation and exposure from the acrylic resin to cells are related to higher production of proinflammatory cytokines and extracellular matrix proteins.
Keywords: Eye; Materials testing; Methylmethacrylate